Implications of therapeutic touch and relaxation massage on aging - Micillo, Glaucia Pegorari; Garcia, Nair Nunes; Alonso, Angelica Castilho; Montiel, José Maria; Bastos, Marta Ferreira (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: The social, technological and scientific advances mainly linked to the health area were important for increasing the longevity of the world population, which highlights the need for studies and public policies aimed at the prevention and treatment of chronic diseases associated with aging. The search for complementary therapeutic techniques and practices to improve the quality of life of the elderly has increased in order to decrease the complications of the aging process such as chronic pain, fatigue, changes in sleep quality, stress/anxiety, depression and the risk of polypharmacy. Objective: Discuss the importance of touch in the elderly and the implications of using this therapeutic technique in improving the quality of life of the elderly. Methods: Through bibliographic review, it was selected studies on touch and its implications on the physical, emotional and sentimental aspects of the elderly’s life. There are several methodologies that use touch as a trigger for benefits to the body, such as: therapeutic touch, reiki and relaxation massage. However, massage has been strongly considered in the scientific literature, especially as it is a non-invasive and non-medicated technique, based on slips, friction, compression and stretches with different intensities and in certain regions of the body that promote improvement of physical aspects, such as: increased blood flow, with consequent increase in oxygenation and the arrival of nutrients to the tissues. Conclusion: It is possible to suggest that the beneficial influence of massage on physical, emotional and sentimental aspects may provide an improvement in the quality of life of the elderly.